Price risk management using by a specified futures model - Kozár , László (Applied Studies in Agribusiness and Commerce, 2010)
The principal achievement of this paper is to introduce the operation of a specified ‘Futures’ model and it’s practice for decision makers of financial institutes through an example based on the price data’s of grain futures market from EU assessment 2004 to these days in Hungary. Based on a theoretical foundation, the calculation model was developed in order to assist short and long-term marketing decisions. The economical basis of the model is the combinative use of two market institutions: public warehousing and futures market. This electronically developed and working model ‘using excel background ‘allows all of the participants of the market: producers, consumers,banks and traders, to use this model in immediate calculations. In addition it helps in order to establish the own business strategy. The model can be used to analyze price influencing factors therefore; it can also be used for policy-making decisions for market participants as well as banks dealing with trade financing activity.